Applications of CRISPR/Cas9 Technology in the Treatment of Lung Cancer. Issue 11 (November 2019) - Jiang, Chunyang; Lin, Xiaohui; Zhao, Zhigang
Abstract : Since its emergence, the application of CRISPR-associated nuclease 9 (Cas9) technology in cancer research has accelerated studies to investigate many aspects of treatment approaches for lung cancer, including the identification of target genes, construction of animal tumor models, and identification of drug resistance-related genes. Moreover, CRISPR/Cas9 can be used in gene therapy for lung cancer, specifically involving molecular targeted drugs and inhibitors. This article reviews the current landscape of CRISPR/Cas9 applications for lung cancer treatment as a basis for further studies. Given its promising performance, in-depth and systematic research on the application of CRISPR/Cas9 in lung cancer treatment will be necessary in future studies for its successful implementation in clinical practice. Highlights: CRISPR/Cas9-mediated gene editing of proto-oncogenes or tumor-suppressor genes offers great potential as a treatment for lung cancer. Drug resistance to chemotherapy is the main reason for the poor efficacy of current treatments for patients with lung cancer. CRISPR/Cas9 gene editing technology can be used to evaluate genes targeted by chemotherapeutic drugs and to identify new pathways to reduce or eliminate resistance to chemotherapy in lung cancer. Targeted drug therapy, which involves several genes such as EGFR, ALK, and KRAS, has become an important approach in lung cancer treatment. However, drug resistance is a growing concern. CRISPR/Cas9 can lower the resistance of tumors to these molecular targeted drugs or inhibitors by editing related genes, which will benefit patients with lung cancer.